Microalgal cell disruption for biofuel development - Halim, R.; Harun, R.; Danquah, Michael; Webley, P. (Elsevier, 2012)
The production of alternative fuels from microalgae involves lengthy processing steps. Cell disruption is an integral part of the downstream pool of unit operations as it facilitates the release of intracellular products essential for biofuel production. This study investigated the use of high-pressure homogenization, ultrasonication, bead beating, and sulfuric acid treatment as laboratory-scale disruption methods for microalgal cells. The performance of each cell disruption method was evaluated in terms of two key indicators: reduction in the intact cell count and reduction in the average colony diameter. The microalgal strain, Chlorococcum sp., was used throughout the study. The most effective disruption was obtained using high-pressure homogenization (average disruption = 73.8% of initial intact cells) followed by sulfuric acid treatment (average disruption = 33.2% of initial intact cells) and bead beating (average disruption = 17.5% of initial intact cells). Even though ultrasonication failed to disrupt the microalgal cells under the investigated conditions (average disruption = 4.5% of initial intact cells), it still managed to disintegrate cellular colonies.